Pediatric Interventional Neuroradiology: Opportunities and Challenges - Cene Jerele; Dimitrij Lovrič; Dimitrij Kuhelj (MDPI AG, 2023)
Pediatric interventional neuroradiology (PINR) is a relatively new field of diagnostic and therapeutic care in the pediatric population that has seen considerable advances in recent decades. However, it is still lagging behind adult interventional neuroradiology due to a variety of reasons, including the lack of evidence validating pediatric-specific procedures, the relative absence of pediatric-specific equipment, and the challenges in establishing and maintaining PINR competencies in a relatively small number of cases. Despite these challenges, the number and variety of PINR procedures are expanding for a variety of indications, including unique pediatric conditions, and are associated with reduced morbidity and psychological stigma. Continued technological advances, such as improved catheter and microwire designs and novel embolic agents, are also contributing to the growth of the field. This review aims to increase awareness of PINR and provide an overview of the current evidence base for minimally invasive neurological interventions in children. Important considerations, such as sedation, contrast agent use, and radiation protection, will also be discussed, taking into account the distinct characteristics of the pediatric population. The review highlights the usefulness and benefits of PINR and emphasizes the need for ongoing research and development to further advance this field.